BASIC COMPONENTS OF STRATEGIC PLANING OF PRECARPATIAN REGION LOCAL COMMUNITIES DEVELOPMENT IN TERMS OF EUROPEAN UNION INTEGRATION PROCESS - Maksymovych , O. V.; Kropelnytska , S.O.; Medynska , T.V. (The actual problems of regional economy development, 2019)
The article is devoted to the sociological data analysis, considering local communities strategic planning analytical support in terms of their advantages as well as disadvantages studying based on particular local community case analysis, involving both qualitative and quantitative methodological approach. Scientific data, devoted to the local communities inhabitans’ cultural and consciousness patterns (based on S. Schwartz’s value profiles theory as well as the cultural dynamic and evolution concept provided by V. Graves, D. Beck, K. Kovan), is introduced in the article. The analytical background, considering Ukrainian, former Soviet Union and Western European countries data is been provided. A number of indicators such as institutional tolerance, satisfaction, subjectivity, social participation and everyday practices have been analyzed. It has been concluded, that in order to implement effectiveness of local communities strategic planning process a range of approaches based on social and cultural identity of Precarpathian region should be provided.